The effect of job stress and job motivation on employees’ performance through job satisfaction (A study at PT. Jasa Marga (Persero) Tbk. Surabaya - Gempol branch) - Noermijati Noermijati; Diana Primasari (Universitas Hayam Wuruk Perbanas, 2015)
Job stress and motivation has a critical role to enhance female employee performance. The research attempts to analyze the direct effect of job stress and motivation on employee performance, and indirect effect of job stress and motivation on employee performance through job satisfaction. This research involves 108 married female employees, with minimal one year working period, as the population and respondents (census sampling). Using Path analysis, it was found that job stress have significant negative effect on employee performance. Motivation has a significant positive effect on employee performance. Job stress does not have an effect on job satisfaction. Motivation significantly positive influences job satisfaction. Job satisfaction significantly influences employee performance. Job stress does not have indirect effect on employee performance through job satisfaction. Motivation has an indirect effect on employee performance through job satisfaction. Motivation has the most important role to enhance employee performance. As an implication, company must give more attention and enhance employee motivation, especially on fulfilling self actualization need.